2015
DOI: 10.1007/s11218-015-9315-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers’ implicit and explicit attitudes toward obesity influence their judgments of students

Abstract: Obese children experience disadvantages in school and discrimination from their teachers. Teachers' implicit and explicit attitudes have been identified as contributing to these disadvantages. Drawing on dual process models, we investigated the nature of pre-service teachers' implicit and explicit attitudes, their motivation to respond without prejudice, and how attitudes influence their judgments of an obese student. Results showed that implicit anti-obesity bias might stem from an implicit positivity toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…It might be that our participants simply do not hold negative stereotypical expectations towards overweight students. Research has shown that a positivity bias towards thinness is more likely responsible for often found anti-obesity biases (Glock et al 2016;Roddy et al 2010). However, if this explanation holds, we should have found more favourable academic judgments of normal-weight students.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…It might be that our participants simply do not hold negative stereotypical expectations towards overweight students. Research has shown that a positivity bias towards thinness is more likely responsible for often found anti-obesity biases (Glock et al 2016;Roddy et al 2010). However, if this explanation holds, we should have found more favourable academic judgments of normal-weight students.…”
Section: Discussionmentioning
confidence: 57%
“…Such high intrinsic motivation to control stereotypical thinking has already been observed among preservice teachers (Glock et al 2016). Intrinsic motivation to suppress stereotypes leads to chronic stereotype suppression and faster responses to stereotype inconsistent information (Wyer et al 2000).…”
Section: Discussionmentioning
confidence: 72%
“…Previous researchers have documented that fashion design and merchandising students (Christel, 2014; Rudd, Harmon, Heiss, & Buckworth, 2015) hold antifat attitudes and negative stereotypes similar to those in the general population (Puhl & Heuer, 2009). Moreover, like other future professionals (e.g., preservice teachers, premed students; Glock, Beverborg, & Müller, 2016; Phelan et al, 2015), fashion and merchandising students’ beliefs toward individuals with large bodies (Christel, 2014; Rudd et al, 2015) are quite negative, which may contribute to the segregation and misrepresentation of plus-size apparel. Christel (2016) suspects that weight bias is an underlying mechanism for decision-making in the fashion industry as many designers and merchandisers harbor negative stereotypes toward obese individuals, finding them unattractive and inferior to thinner bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes have been shown to be negative among physical education teachers (Fontana et al, 2013;Greenleaf & Weiller, 2005;Lau et al, 2018;Lynagh et al, 2015;O'Brien et al, 2007) and even among teachers in academic subjects (Lau et al, 2018;Lynagh et al, 2015). Negative attitudes were found to predict judgments of overweight students' language proficiency and intelligence, as preservice teachers with more negative attitudes were found to make more negative judgments of overweight students on these dimensions (Glock et al, 2016).…”
Section: Stereotypes Of Overweight Individualsmentioning
confidence: 99%